PENGUKURAN KINERJA DALAM KONVERSI SAMPAH TPA MENJADI SUMBER ENERGI ALTERNATIF: PENGUKURAN KINERJA DALAM KONVERSI SAMPAH TPA MENJADI SUMBER ENERGI ALTERNATIF - Aris Puja Widikda; Farid Mujayyin; Nugrahadi DM (Jurnal Teknologi dan Terapan Bisnis, 2022)
Waste to RDF (Waste Derived Fuel) waste processing technology involves several steps, including sorting the waste, grinding the waste until it is dry, and molding the dried waste into waste briquettes. The aim of this research is to determine the optimal production process, so it is necessary to determine KPI (Key Performance Indicator). Waste processing operational standards at RDF are maximized using six sigma DMAICs including establishing RDF production standards, measuring machine capabilities, identifying the main causes of machine failure, determining improvements and accelerating production as well as controlling the production process. In this research, the cause of poor engine performance can be determined to be due to the pressure exerted on the crusher which often stops after being repaired. KPI Target Results Delivery of RDF to the factory twice a day, Availability level 85%, Efficiency level 88%, Quality level 86%, Number of mechanics 1 person, increased inspections twice a day, reduced downtime 2 times/month, number of routine maintenance 3 times , number of tools/spare parts 10 pcs, defective product 5 kg. After carrying out calculations, the OEE (Overall Effective Equipment) value can be determined and optimized. Based on the OEE value it reaches 94%. While the objective KPI (key performance indicator) using the scorcade balance method is waste treatment technology which is evaluated from a production capacity of 4 tons/hour